Устройство для смещения электронов и коррекции поля в момент инжекции - Ананьев Л. М. Лев Мартемьянович; Отрубянников Ю. А.; Чахлов В. Л. Владимир Лукьянович; Шестаков В. Г. (1966, 1966)
В фонде НТБ ТПУ отсутствует